Consciousness and self in language: a view from cognitive semiotics - Abrantes, Ana Margarida (TECCOGS: Revista Digital de Tecnologias Cognitivas, 2021)
Consciousness is a subjective experience. To science it matters little whether there is an agent behind conscious experience – things like holding a belief, making a decision, remembering a person, attend to an object, act in a situation –; science (in this case neuroscience) is instead concerned with describing what processes in the brain are responsible for that experience. And yet we believe that we are agents of these experiences, that they are not the mechanical outcome of a series of such causal processes. This belief underlies and gives meaning to our individual existence and it is foundational to various aspects of social reality. When studying cognition and mental life, we cannot do without subjective experience. It may not be observable as its neural substrate is, but it is nonetheless real, as experience, and moreover reportable in a semiotic exchange, mediated, among other means, through language. Language, in turn, is hardly ever purely referential: instead language invites shared attention to a common object of reference, and it can be a means of modeling or manipulating an interlocutor’s conceptual viewpoint over that referent. This paper explores this relationship between consciousness, the experience of a self and how this experience is shaped by intersubjectivity. These issues will be approached from a linguistic angle, namely through a cognitive semiotic analysis of self-reference and intersubjective reference. It is proposed that the representation of the self, as it is available in linguistic expression, relies on construal and perspective, an alternative account to a conceptualization of the person based on a differentiation between self (bodily, social) and subject (agent of consciousness, belief, feeling), and on a metaphorical projection between these. Moreover, it is suggested that a conceptualization of the self contingent on external perspective is a manifestation of theatricality, a strategy by which an object of reference is performed on a mental stage, towards which interlocutors jointly gear their attention. Keywords: self; subject; cognitive semiotics; language; theatricality.